Positive parenting, career aspirations, and exploration: A study of third-year urban undergraduate students - Sawitri, Dian Ratna; Kaloeti, D. V. S.; Kustanti, Erin R.; Qonitatin, Novi; Nurhayati, Niken F.; Hidayati, Frieda N. R. (UI Scholars Hub, 2021)
Career exploration reflects activities conducted to collect information about oneself and potential occupations to become self-aware and understand the job market. Career exploration guides the realization of career aspirations and is thus crucial for young adults. It helps the youth make appropriate career-relevant decisions. However, it is unknown whether career aspirations mediate the links between positive parenting and career exploration activities undertaken by urban thirdyear undergraduate students. This study aimed to bridge this gap in the literature, and to this end, a survey was administered to 125 third-year undergraduate students attending a state university in Semarang, Central Java. The Career Exploration Scale, Career Aspirations Scale, Positive Parenting Subscale, and questions on demographic characteristics were employed for data collection. Structural equation modeling demonstrated that career aspirations fully mediated the path between positive parenting and career exploration. The findings of this study underline the importance of career aspirations in translating the effects of positive parenting into specific career exploration activities undertaken by college students. Finally, suggestions based on the study results are offered for third-year undergraduate students, parents, and practitioners.